Fulvic acid application increases rice seedlings performance under low phosphorus stress - Lv, Xiaomeng; Li, Qingchao; Deng, Xuan; Ding, Shitao; Sun, Ruibo; Chen, Shunquan; Yun, Wenjing; Dai, Changrong; Luo, Bingbing (BMC plant biology, 2024)
Fulvic acid enhances plant growth and interacts synergistically with phosphate fertilizer to alleviate the agricultural production problem of low phosphorus fertilizer utilization efficiency. However, the underlying mechanism of its action remains poorly understood. In this study, we investigated the impact of fulvic acid application with varying concentrations (0, 40, 60, 80 and 120 mg/L) on rice performance in plants grown in a hydroponic system subjected to low phosphorus stress. The rice growth phenotypes, biomass, root morphology, phosphorus uptake, and the impact of fulvic acid on the rhizosphere environment of rice, were assessed. The findings showed that adding appropriate concentrations of exogenous fulvic acid could promote the growth performance of rice under low phosphorus stress. Particularly at T1 (40 mg/L) and T2 (60 mg/L) over the control effectively increased rice biomass by 25.42% and 24.56%, respectively. Fulvic acid treatments stimulated root morphogenesis, up-regulated phosphate transporter genes, and facilitated phosphorus absorption and accumulation. Especially T1 (20.52%), T2 (18.10%) and T3 (20.48%) treatments significantly increased phosphorus uptake in rice, thereby alleviating low phosphorus stress. Additionally, fulvic acid elevated organic acids concentration in roots and up-regulated plasma membrane H -ATPase genes, promoting organic acids secretion. This metabolic alteration can also alleviate low phosphorus stress in rice. The effect of exogenous fulvic acid on physiological indicators is concentration-dependent under low phosphorus stress, enhances rice performance and reduces reliance on phosphorus fertilizer. This provides new insights to shed light on the mechanism of alleviating low phosphorus stress in rice through fulvic acid application, an eco-friendly tool.